2010
DOI: 10.1007/s00198-010-1336-9
|View full text |Cite
|
Sign up to set email alerts
|

International variation in proximal femur bone mineral density

Abstract: International variation in hip BMD does exist, with international and between-centre differences being less evident at the femoral neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
5
1
1
Order By: Relevance
“…On average, our subset was broadly similar to the full population in terms of baseline characteristics, but the women in our subset did have higher total hip BMD (P< 0.001) and higher broadband ultrasound attenuation at the heel (P<0.01) (post hoc analysis). However, site-specific differences in BMD were observed across the whole of the OPUS study [22]. Nevertheless, the incidence of vertebral fracture in our subset may have been lower than might have been observed in the full baseline population; thus, our results may not be directly applicable to the wider population.…”
Section: Discussioncontrasting
confidence: 44%
“…On average, our subset was broadly similar to the full population in terms of baseline characteristics, but the women in our subset did have higher total hip BMD (P< 0.001) and higher broadband ultrasound attenuation at the heel (P<0.01) (post hoc analysis). However, site-specific differences in BMD were observed across the whole of the OPUS study [22]. Nevertheless, the incidence of vertebral fracture in our subset may have been lower than might have been observed in the full baseline population; thus, our results may not be directly applicable to the wider population.…”
Section: Discussioncontrasting
confidence: 44%
“…This is different from studies in other countries. In previous studies, European between-center differences in BMD were observed in the European Vertebral Osteoporosis (EVO) 9 , the Network in Europe on Male Osteoporosis (NEMO) 10 and the Osteoporosis and Ultrasound study (OPUS) 12 . In a study published in 1997 9 of 16 European populations, both males and females aged between 50 and 80 were recruited randomly from local population registers.…”
Section: Discussionmentioning
confidence: 99%
“…For men, age-adjusted total hip BMD was lower in Bergen compared with Tromsø. In 2011 12 , proximal femur BMD of females aged 20–39 (n = 258) and males aged 55–79 (n = 1,426) from three European centers were compared. A clear geographical difference in hip BMD did exist; however, there was less evidence for femoral neck BMD 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current standard-of-care for predicting fracture risk using FRAX™ (Kanis et al 2009), dual-energy X-ray absorptiometry scan-based areal bone mineral density (DXA-aBMD) measured at the femoral neck is used as a surrogate measure of bone strength. Ageing is another risk factor, as it leads to progressive losses in bone strength (Paggiosi et al 2011) and in neuro-motor control (Larsson and Ramamurthy 2000) which can cause fall frequency to increase. Ensrud (2013) recently described in detail the epidemiology of hip fracture risk with advancing age.…”
Section: Introductionmentioning
confidence: 99%